Distribution of 131I-cytotoxin 14 from Naja naja atra venom in rats - Guo Mu-ping; Wang Qing-chuan; Liu Guang-fen (Acta Pharmacologica Sinica, 2016)
Cytotoxin 14 (CT14) from Naja naja atra venom was labelled with 131I by chloramine-T method and its tissue distribution was studied in rats. The highest concentration of the cytotoxin was found in kidney, 5979 dpm per mg weight, 14 times more than that of the control animals, at 0.5 h after i.v. injection and high concentrations were found in liver, spleen, pancreas, and adrenal. CT14 was also found in brain at 2 h after injection, 50 dpm per mg weight, 3 times more than that of the control